PREDICTION OF CARBON DIOXIDE GAS DIFFUSION IN THE CALDERA OF MOUNT BATUR, BALI BASED ON CONCENTRATION OF SOIL GAS, RADON, AND DISSOLVED GASES - Rozani, Fathan
CO2 gas as one of the components of volcanic gas can be released from magma through active volcanic craters or occur diffusionly in the surrounding area. This study aims to predict the presence or absence of CO2 gas diffusion in the caldera area of Mount Batur, Bali based on the concentration of soil gases, radon, and dissolved gases in the manifestation water. Measurement of radon gas concentration is carried out directly in the field and soil gas concentration testing is carried out using Gas Chromatography. Concentration of dissolved CO2 was measured using the Total Alkalinity Test from the manifestation water sample present in the study area. The concentration of CO2 in soil gas is valued between 480-774 ppm and the concentration of radon gas is worth between 120-1887.5 Bq/m3. Dissolved CO2 concentrations are 5.28-5150.96 ppm and dissolved radon gas concentrations are between 0-1173.46 Bq/m3. Analysis of radon gas concentrations indicated the presence of permeable zones on the north and south sides of the caldera, and non-permeable zones on the area around the crater to the bottom of the caldera. The presence of permeable zones is not correlated with the concentration of CO2 gas. The average concentration of CO2 gas in soil gas is higher than the concentration of CO2 gas in the atmosphere and some other volcanic areas, so it can be predicted that there is a diffusion of CO2 gas in the caldera of Mount Batur, but it is unknown about how much CO2 degassed from magma and the rate of diffusivity is not measured.